The prevalence of vitamin D deficiency among Saudis and non-Saudis, diabetics and non-diabetics, and the impact of vitamin d on insulin sensitivity in type two diabetic male patients in Al-Madinah Al-Munawarah / Muhammed Hassan Abdelfatah Nasr - Abdelfatah Nasr, Muhammed Hassan (2019)
Vitamin D, or the “sunshine” hormone became an attractable topic that recently captivates many researchers. The increased prevalence of vitamin D deficiency became an alarming health concern despite the accumulative evidence exploring its crucial role in various body organs. Type 2 diabetes mellitus (T2DM) is a major, progressive health condition that can lead to premature morbidity and mortality. The link between the risk of T2DM, insulin resistance and vitamin D deficiency has perplexed the medical society due to the controversy in the data available. Saudi Arabia (SA) is a sunny region, however ample amount of data reported the increased prevalence of vitamin D deficiency along with T2DM. This huge rise in SA found to be in concordance with the high global rate of both conditions. This study aimed to compare vitamin D deficiency between Saudi and non-Saudi nationalities, between healthy and T2DM patients. It aimed also to assess the possible associated factors for vitamin D deficiency and to study the impact of vitamin D supplementation on insulin resistance, and glycemic control on T2DM male patients living in Al-Madinah Al-Munawarah. This study consisted of three phases. Phase one and two were cross-sectional studies, while phase three was double-blind, randomized control trial. All phases were carried on the Medical Unit, Taibah University.